ANALISIS FAKTOR INTERNAL DAN EKSTERNAL :PENGHAMBAT DAN SOLUSI PERKEMBANGAN KOPERASI(STUDI PADA KOPERASI UNIT DESA DI KABUPATEN MUBA) - Muhammad Wadud; Iwan Efriady (Universitas Indo Global Mandiri)
The location of this study in Musi Banyuasin, while the object of research is the Village Unit Cooperatives in six Districts, Cooperative Village Unit investigated the KUD Sinar Desa, KUD Pembela, KUD Sejahtera, KUD Sandes, KUD Embun Pagi, KUD Pelita, KUD Panca Kerja, KUD Tri Jaya, KUD Sumber Jaya Makmur Lestari and KUD Karya Makmur. Use research methods and research approaches diskriftif fenomenalogi approach. While the research instrument used questionnaires, interviews and surveys. This research activity has resulted in findings that the average KUD studied in healthy condition either simultaneously or partially. The results of the simultaneous study of cooperatives in the top ten there are two healthy KUD the KUD Tri Jaya and KUD Karya Makmur Jaya and cooperatives to obtain scores respectively 81.6 and 80.6. While eight other KUD in reasonably healthy condition with acquisition scores above 65 While the partial results of the calculation of the average rate earned on internal factors and external factors on each of the Cooperative are very varied. Through the above data if each of these cooperative complies with the Cooperative management, both from the internal and external side. If seen from the average achieved in the calculation of the internal factors there are four cooperatives that have Quality of human resources, as well Implement Cooperative Principle, system administration and good business. The cooperatives are cooperatives Prosperous scores 81, KUD Pelita scores 81, KUD Tri Jaya scores 81.67 and 81 scores Karya Makmur that KUD While having a score of 58.33 which is KUD Sinar Desa , the low value of the score obtained in the cooperative course is determined by the specified indicators. Based on the results of research studies and results indicators SWOT analysis can be seen that the main problem lies in the KUD only: Low Capital, Low Quality Board, Lack of Information on cooperative management, lack of capacity and skills in the field of administration and management of financial To overcome these problems takes the following steps: Capital Increase and to the board of Cooperative Management Training, Recruitment and Appointment of administrators are more selective in who has the education and work experience, improving employee training, facility improvement, especially supporters of the technology, cooperative empowerment Acceleration directionally and integrated, Synergize regional development programs with cooperative work program